KORELASI KADAR D-DIMER DENGAN JUMLAH SINUS VENA SEREBRAL PADA PASIEN CEREBRAL VENOUS THROMBOSIS - Aditya Kurnianto; Yovita Andhitara; Dodik Tugasworo; Retnaningsih Retnaningsih; Rahmi Ardhini; Vivi Kristiani Rumapea; Jethro Budiman (PERDOSNI, 2020)
Introduction: Cerebral venous thrombosis (CVT) is a rare yet potentially devastating disease. According to the Virchow Triad, one of the predisposing factors is the hypercoagulable state of the blood that can be measured with D-dimer. Aim: To evaluate the correlation of D-dimer level and number of venous sinus in patient with CVT. Methods: A retrospective study including 45 patients with CVT between January 2019-January 2020 in Dr. Kariadi General Hospital, Semarang were conducted. The diagnosis of CVT was confirmed by digital subtraction angiography (DSA). Data on coagulation profile including platelet count, prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen level, and d-dimer level were collected. The correlation between the D-dimer level and the number of the venous sinus was analyzed by Spearman’s rank correlation test. Results: Most of the sample were female with the mean age of 39.6 years. Multiple venous sinus occurred in 24 patients, and the most location of the CVT was sagittal sinus. The mean platelet count was 296,000cells/mcL, mean fibrinogen 326.9mg/dL, mean APTT 34s, mean PT 12.4s, and the median D-dimer level was 556.5ng/mL. There was a moderate correlation of D-dimer level and number of venous sinus (p=0.000, r=0.529). Discussion: D-Dimer level in CVT patients were elevated. The increased level of D-dimer was associated with multiple cerebral venous sinus in CVT patients because the extension of thrombosis causing an increase in D-dimer level. Keywords: coagulation, CVT, D-dimer, cerebral venous sinus